NOTES ON THE ROSEATE TERN Sterna dougallii BREEDING IN KARIMUNJAWA ISLANDS, JAVA, INDONESIA - Hary Susanto; Imam Taufiqurrahman; Tulus Wicaksono Bayu Aji (BRIN Publishing (Penerbit BRIN), 2024)
Roseate Tern Sterna dougallii is a rare to uncommon resident and migrant species in Greater Sundas, with only a handful records in Java. On 24 May 2021, a nest containing a single egg of the species was found in Karang Ketel islet, Karimunjawa Islands and constitute the first breeding record of Roseate Tern in the area, filling the breeding information gap of the species in Java for about 80 years since it first reported. Follow up surveys after the findings carried out for three consecutive years from May 2021-June 2023, reveals the species regularly breeding in three locations, i.e., Karang Ketel islet, Karang Kapal islet, and Krakal Besar I. Breeding recorded from May to August, with only small colony of 2-20 birds present.